A pragmatic randomised controlled trial of an implementation intervention to increase healthy eating and physical activity-promoting policies, and practices in centre-based childcare services: study protocol. Issue 5 (21st May 2015) - Finch, Meghan; Yoong, Sze Lin; Thomson, Rebecca J; Seward, Kirsty; Cooney, Mairead; Jones, Jannah; Fielding, Alison; Wiggers, John; Gillham, Karen; Wolfenden, Luke
Abstract : Background: Promotion of healthy eating and physical activity in early childhood is recommended as a global chronic disease prevention strategy. Centre-based childcare services represent a promising setting to provide children with opportunities to improve healthy eating and physical activity. Evidence to inform implementation of childcare obesity prevention guidelines into routine practice in childcare, however, is lacking. This study aims to assess the effectiveness of an intervention, delivered to childcare staff, aiming to increasing service implementation of healthy eating and physical activity-promoting policies and practices. Methods and analysis: A pragmatic parallel group randomised controlled trial will be undertaken with 165 childcare services in the Hunter New England region of New South Wales, Australia. Services will be randomised to receive either a 10-month evidence-based performance review intervention with other resources to support practice change, or to a waitlist control group. The primary trial outcome is the proportion of services implementing all of the following recommended healthy eating and physical activity promoting practices: written nutrition, physical activity and small screen recreation policies; providing information to families regarding healthy eating (including breastfeeding), physical activity and small screen time; providing twice weekly healthy eating learning experiences to children; providing water and only plain milk to children; providing fundamental movement skills activities for children every day; and limiting and using electronic screen time more for educational purposes and learning experiences. Effectiveness will be assessed using a telephone interview of practice implementation with childcare staff at baseline and 12 months following baseline. Ethics and dissemination: The study was approved by the Hunter New England Human Research Ethics Committee and the University of Newcastle Human Research Ethics Committee. Study findings will be disseminated widely through peer-reviewed publications and conference presentations. Trial registration number: Australian New Zealand Clinical Trials Registry ACTRN12614000972628.